2013
DOI: 10.1126/scitranslmed.3005361
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic and Immunotherapeutic Vaccinia Induces Antibody-Mediated Complement-Dependent Cancer Cell Lysis in Humans

Abstract: Oncolytic viruses cause direct cytolysis and cancer-specific immunity in preclinical models. The goal of this study was to demonstrate induction of functional anticancer immunity that can lyse target cancer cells in humans. Pexa-Vec (pexastimogene devacirepvec; JX-594) is a targeted oncolytic and immunotherapeutic vaccinia virus engineered to express human granulocyte-macrophage colony-stimulating factor (GM-CSF). Pexa-Vec demonstrated replication, GM-CSF expression, and tumor responses in previous phase 1 tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 69 publications
1
68
0
Order By: Relevance
“…Pexa-Vec utilizes the unique characteristics of vaccinia, which allows the virus to survive in the bloodstream in the presence of neutralizing antibodies, leading to its ability to be administered both intravenously and intratumorally (Kim et al 2006). Pexa-Vec has shown proof-of-concept mechanisms in clinical trials for cancer patients, including HCC patients Park et al 2008;Hwang et al 2011;Kim et al 2013). Notably, Liu et al (2008) showed that HCC tumor tissue could serve as a source of acute HBV replication and posttreatment HBV release, and that Pexa-Vec can suppress underlying HBV replication in HCC patients.…”
Section: Oncolytic Virus Therapymentioning
confidence: 99%
“…Pexa-Vec utilizes the unique characteristics of vaccinia, which allows the virus to survive in the bloodstream in the presence of neutralizing antibodies, leading to its ability to be administered both intravenously and intratumorally (Kim et al 2006). Pexa-Vec has shown proof-of-concept mechanisms in clinical trials for cancer patients, including HCC patients Park et al 2008;Hwang et al 2011;Kim et al 2013). Notably, Liu et al (2008) showed that HCC tumor tissue could serve as a source of acute HBV replication and posttreatment HBV release, and that Pexa-Vec can suppress underlying HBV replication in HCC patients.…”
Section: Oncolytic Virus Therapymentioning
confidence: 99%
“…In the majority of cases, the most effective OV treatments combine potent viral oncolysis with induction of a specific immune response against tumor antigens, as shown in several clinical and preclinical studies (9)(10)(11)(12). The mechanisms how OV therapies elicit antitumor immune responses are not clearly understood yet, but likely involve the capture of released tumor antigens by bystander antigen-presenting cells (APC) following tumor cell lysis (13).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation within tumors was detected following intratumoral Pexa-Vec administration in patients with melanoma [17,26]. Furthermore, functional anti-cancer immunity in the context of Pexa-Vec treatment was demonstrated by measuring induction of antibody-mediated complement-dependent cytotoxicity (CDC) utilizing a panel of tumor cell lines of different histologies [24,48 ]. Furthermore, T cell responses to b-galactosidase peptides were detected in HCC patients treated with Pexa-Vec, as shown by Enzyme-Linked ImmunoSpot (ELISPOT) analysis; this provides proof-of-concept that T cell responses can be induced to transgenes encoded by oncolytic vaccinia viruses [24].…”
Section: Support For Immunotherapeutic Potential Of Oncolytic Vaccinimentioning
confidence: 99%